Prehospital ECG Interpretation Methods for ST-Elevation MI Detection and Catheterization Laboratory Activation: A Systematic Review and Meta-Analysis. - Alrawashdeh, Ahmad; Ihtoub, Samar; Alkhatib, Zaid I.; Alwidyan, Mahmoud; Khader, Yousef S.; Rawashdeh, Sukaina; Alqahtani, Saeed; Stub, Dion; Alhamouri, Rahaf; Alkhazali, Islam E.; Nehme, Ziad (Archives of Academic Emergency Medicine, 2025)
Introduction: The diagnostic accuracies of different electrocardiography (ECG) interpretation methods remain unclear. Therefore, this study aimed to systematically evaluate and compare the diagnostic accuracy of prehospital 12-lead ECG interpretation methods for identifying ST-elevation myocardial infarction (STEMI) and activating cardiac catheterization laboratories (CCLs). Methods: A comprehensive search was conducted in Medline, Scopus, and CINAHL databases up to August 2024. Two reviewers independently selected studies that assessed the diagnostic accuracy of prehospital 12-lead ECG in real-time STEMI identification and CCL activation. Pooled estimates of sensitivity, specificity, diagnostic odds ratio (DOR), and area under the curve (AUC) were calculated using bivariate generalized mixed-effects regression models or random-effects meta-analysis as appropriate. The quality of the included studies was assessed using the QUADAS-2 tool. Results: Thirty-six studies involving 67,168 patients were included. Overall, for STEMI identification, the pooled AUC of ECG was 0.96 (95%CI:0.94–0.98), sensitivity was 80% (95% CI, 69–88%), specificity was 97% (95%CI: 94–98%), and DOR was 114 (95%CI: 59–222). Ambulance clinicians achieved the highest DOR (264; 95%CI: 33–2125), followed by transmission method (136; 95%CI, 59–312) and computer-assisted analysis (78; 95%CI: 33–186). Transmission method demonstrated superior specificity (0.98; 95%CI: 0.94-0.99) and the lowest rates of inappropriate (13.2%; 95% CI: 8.6%–19.2%), and false-positive (11.0%; 95%CI: 6.9%–15.0%) CCL activations. Conclusion: All prehospital ECG interpretation methods yielded acceptable diagnostic accuracy for STEMI identification; however, transmission offered the greatest specificity and fewer unnecessary CCL activations. Adopting transmission-based strategies, where feasible, and enhancing training and decision support for ambulance clinicians may improve prehospital STEMI detection and resource utilization.